2017
DOI: 10.12816/0034635
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians as Bioindicators of the Health of Some Wetlands in Ethiopia

Abstract: Background: Ethiopia has a variety of wetlands which provide enormous socioeconomic and environmental values. Most of these wetlands are under severe pressure and degradation. Maintaining the health of wetlands is recognized as crucial for protecting biodiversity, ecosystem function, and human health. In order to properly protect and conserve wetlands, it is essential to collect baseline data and establish monitoring programs which can detect change in the health of the wetland over time. One common method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 6 publications
0
13
0
3
Order By: Relevance
“…Teferi et al (2010) also reported that geographically isolated wetlands near Choke Mountain were converted into farmlands. This shows that the study area was undergoing serious transformation, with the rapid decline of wetland's health (Saber et al, 2017;Scott & Jones, 1995). Particularly, unsustainable activities such as converting wetlands into agricultural and grazing lands were occurring elsewhere in Ethiopia (Amsalu & Addisu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Teferi et al (2010) also reported that geographically isolated wetlands near Choke Mountain were converted into farmlands. This shows that the study area was undergoing serious transformation, with the rapid decline of wetland's health (Saber et al, 2017;Scott & Jones, 1995). Particularly, unsustainable activities such as converting wetlands into agricultural and grazing lands were occurring elsewhere in Ethiopia (Amsalu & Addisu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than the observed effect on gonads, atrazine and/or nitrate had a wide range of sever effects concerning growth and body size at metamorphosis [32], genotoxicity [33] or malformations [34], indicating the disrupting action of such chemicals on amphibian development and sexual maturity. Over the years, human activities in agrochemical use have increased causing disturbances to all organisms in the ecosystem either in direct or indirect route, while the high concentrations were detected as well as low concentrations [35]; by this approach the present study can be a good assessment for relevant chronic high exposure.…”
Section: Discussionmentioning
confidence: 90%
“…De otro lado, se cree que un pequeño porcentaje de las especies observadas está dentro de poblaciones con dinámicas que van en aumento, lo que sugiere una posible recuperación de esta zona a lo largo del tiempo, dado que se sabe que ha atravesado por un proceso de sucesión ecológica que ha permitido una modificación ordenada sobre su entorno físico, el cual ahora está representado por un bosque secundario (Fonseca & Mahecha, 2018). Además, se sabe que la presencia de anfibios es un excelente bioindicador del estado de salud y recuperación de un ecosistema (Houston et al, 2018;Saber et al, 2017), por lo que se ha observado que familias como Hylidae, Hylodidae, Leiuperidae y Bufonidae tienen una eficiencia mayor al 60 % como bioindicadores para dichos estados (Campos et al, 2014).…”
Section: Resultsunclassified